Estimating Present Bias and Sophistication over Effort and Money - Claudia Cerrone; Anujit Chakraborty; Hyok Jung Kim; Leonhard K. Lades (University of California, Department of Economics, 2023)
We design and implement the first real-effort experiment that can jointly estimate present bias (Ø) and sophistication (bØ), with separate preference parameters for money (Øm, bØm) and effort (Øe, bØe). In our study, participants chose to (and predicted to) complete 14% (and 10%) fewer tasks on the same day than on a future day, leading to an estimated Øe between 0.70 and .79 (and bØe between 0.80 and .88). Participants chose to (and predicted to) complete 2% (and 2%) fewer tasks when the payment happened on the same day than on a future date, implying insignificant present bias or sophistication over money. At the individual-level, estimates of Øe and bØe are highly correlated but that of Øm and bØm are uncorrelated. We explain and illustrate how assuming identical preferences for money and effort, biases the estimates of key preference parameters.
Keywords: C91; D81; D90; 330; time preferences; present bias; sophistication